Pre-service primary teachers' perceptions of gamification as a methodology - Ernesto Colomo Magaña; Alejandro Colomo Magaña; Andrea Cívico Ariza; Lauren Basgall (Journal of Technology and Science Education, 2024)
Gamification involves making teaching processes fun with the intention of improving factors that affect learning, such as motivation. Although the focus is not on the game itself and the corresponding entertainment, its design and results provide an alternative for developing educational proposals that make students the protagonists and generate student engagement with their education. On that basis, this study aims to understand pre-service primary school teachers’ perceptions of gamification as an active methodology, taking the gender and time of analysis variables into account. To this end, a quantitative longitudinal panel design (pre-test and post-test) from a descriptive and inferential approach was applied. The sample consisted of 284 pre-service primary education teachers from the University of Málaga (2021/2022 academic year). The information was collected through a validated instrument that measures perceptions of both digital didactic resources and teaching methodologies. The results revealed positive perceptions of gamification as a methodology, with a significant improvement from the pre-test to post-test scores. As for the analysis of the gender variable, there were significant differences, with the male participants’ ratings of gamification being higher than those of the female participants. In conclusion, gamification constitutes a feasible methodology to implement due to being well-received by university students, as a result of its motiving and fun nature and the fact that it makes students the protagonists of the learning process.